A hybrid heuristic approach to solve the multi level capacitated lot sizing problem - Toledo, Claudio Fabiano Motta; De Oliveira, Renato Resende Ribeiro; Franca, Paulo Morelato [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents preliminary results found by a hybrid heuristic applied to solve the Multi-Level Capacitated Lot Sizing Problem (MLCLSP). The proposed method combines a multi-population genetic algorithm and fix-and-optimize heuristic. These methods are also integrated to a mathematical programming approach. For this, a mathematical reformulation of MLCLSP model is proposed to embed the exact solution of the model in the heuristic approaches. The hybrid heuristic is evaluated in two sets of benchmark instances. The solutions found are compared with those reached by other methods from literature. The preliminary results obtained indicate that the hybrid heuristic outperforms other approaches in the majority of problems solved. © 2011 IEEE.
Keywords: Genetic algorithms; Heuristic algorithms; Lot sizing; Optimization; Production planning